Answer:
Resultant force = 70.71067811865 pounds
Step-by-step explanation:
Pythagoras theorem is used to calculate the resultant force since the angles between two wires is 90⁰
Resultant force² = 50² + 50² = 5000
Resultant force = (5000)¹/² = 70.71067811865 pounds
Answer: A,C,E
Step-by-step explanation:
i just answered the question
Answer: its b because once u simplify everything it amounts to b
<span>The number of dollars collected can be modelled by both a linear model and an exponential model.
To calculate the number of dollars to be calculated on the 6th day based on a linear model, we recall that the formula for the equation of a line is given by (y - y1) / (x - x1) = (y2 - y1) / (x2 - x1), where (x1, y1) = (1, 2) and (x2, y2) = (3, 8)
The equation of the line representing the model = (y - 2) / (x - 1) = (8 - 2) / (3 - 1) = 6 / 2 = 3
y - 2 = 3(x - 1) = 3x - 3
y = 3x - 3 + 2 = 3x - 1
Therefore, the amount of dollars to be collected on the 6th day based on the linear model is given by y = 3(6) - 1 = 18 - 1 = $17
To calculate the number of dollars to be calculated on the 6th day based on an exponential model, we recall that the formula for exponential growth is given by y = ar^(x-1), where y is the number of dollars collected and x represent each collection day and a is the amount collected on the first day = $2.
8 = 2r^(3 - 1) = 2r^2
r^2 = 8/2 = 4
r = sqrt(4) = 2
Therefore, the amount of dollars to be collected on the 6th day based on the exponential model is given by y = 2(2)^(5 - 1) = 2(2)^4 = 2(16) = $32</span>
Answer:
{x,y,z} = {-18,4,2}
Step-by-step explanation:
Solve equation [2] for the variable x
x = -10y + 2z + 18
Plug this in for variable x in equation [1]
(-10y+2z+18) + 9y + z = 20
- y + 3z = 2
Plug this in for variable x in equation [3]
3•(-10y+2z+18) + 27y + 2z = 58
- 3y + 8z = 4
Solve equation [1] for the variable y
y = 3z - 2
Plug this in for variable y in equation [3]
- 3•(3z-2) + 8z = 4
- z = -2
Solve equation [3] for the variable z
z = 2
By now we know this much :
x = -10y+2z+18
y = 3z-2
z = 2
Use the z value to solve for y
y = 3(2)-2 = 4
Use the y and z values to solve for x
x = -10(4)+2(2)+18 = -18